2017
DOI: 10.1111/ahe.12309
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism in jaw muscles of the Japanese sparrowhawk (Accipiter gularis)

Abstract: Materials suitable for anatomical research of raptorial birds are rare. Bird-eating raptors show distinct inter-sexual differences in body size and parental roles. The large females catch larger prey and prepare small morsels to feed their young using their hooked beaks. Here, we investigated the architectural properties of different jaw muscles of the Japanese sparrowhawk (Accipiter gularis) and examined whether there is sexual dimorphism in their architectural design. The results showed that musculus depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Sustaita and Hertel (2013) showed that accipiters and falcons exhibit different bite forces despite similarities in body size and this is associated with increased muscle mass in falcons. In Japanese sparrowhawks ( Accipiter gularis ) the larger females have relatively larger m. pterygoideus that reflects their reversed sexual dimorphism in anatomy and diet (Wang et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sustaita and Hertel (2013) showed that accipiters and falcons exhibit different bite forces despite similarities in body size and this is associated with increased muscle mass in falcons. In Japanese sparrowhawks ( Accipiter gularis ) the larger females have relatively larger m. pterygoideus that reflects their reversed sexual dimorphism in anatomy and diet (Wang et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…PCSA is the volume of the muscle multiplied by the cosine of pinnation angle of the muscle fascicles (≤1) and then divided by the fascicle length. Whilst PCSA is often reported (Carril et al., 2015; Sustaita, 2008; Wang et al., 2017) pinnation angles and fascicle lengths are rarely found in the literature (but see Pestoni et al., 2018; Soons et al., 2012). In some instances, pinnation angles are not considered in the calculation of PCSA (Genbrugge et al., 2011) despite their importance in modelling muscle forces (Martin et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Wang et al . (2017) found in the Japanese Sparrowhawk ( Accipiter gularis ) that the muscles that act on the jaw, m. pterygoideus, had a significantly larger mass and PCSA value in females than in males.…”
Section: Discussionmentioning
confidence: 99%
“…Within this context, there are no studies dealing with musculature and possible presence of RSD with the exception of a recent study on the mandibular muscles of Accipiter gularis Wang et al . (2017). This is a relevant focus given the importance of the beak for this group while obtaining food (e.g., tearing of prey).…”
Section: Introductionmentioning
confidence: 99%
“…Muscle dissection is a way of calculating bite force, but muscle masses in birds are only reported in a relatively few species, including (but not exclusively): cormorants Suliformes, (Burger 1978), birds of prey Accipitriformes and Falconiformes (Sustaita 2008 and see Hull 1991, Wang et al 2017, waterfowl Anseriformes, (Goodman & Fisher 1962), and songbirds Passeriformes, (e.g. van der Meij & Bout 2004).…”
Section: Introductionmentioning
confidence: 99%